Tantangan Kepemimpinan Perempuan dalam Organisasi Fokresi: Penelitian - Septina Purnama Sari Tambunan; Elfira Aginta Br Sitepu; Elvi Natalia Nainggolan; Rotua Sahat P Simanullang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Women in leadership roles have shown significant progress across various sectors, but still face challenges that hinder their career development. Key barriers include gender bias, limited access to guidance or mentorship, and unequal caregiving responsibilities. For example, women tend to be less likely to receive crucial early promotions to management, which determine their leadership career paths. Furthermore, the “glass cliff” phenomenon often occurs, where women are appointed to leadership positions during times of crisis, increasing the risk of failure. Nevertheless, women leaders possess unique strengths such as creativity, empathy, and collaborative skills that are invaluable in driving innovation and organizational success. Overcoming these barriers requires systemic changes in the form of equitable policies, mentorship opportunities, and a supportive work environment that allows women to realize their full leadership potential.